2012
DOI: 10.1007/s12522-012-0125-x
|View full text |Cite
|
Sign up to set email alerts
|

Singleton pregnancy outcomes after assisted and non‐assisted reproductive technology in infertile patients

Abstract: ART procedure may itself be a risk factor for the development of placenta previa. Some of the abnormal perinatal outcomes that had been previously attributed to ART, however, may be due to the baseline characteristics of infertile patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Thirty‐four studies met inclusion criteria (Figure 1). 23–54 There were 33 cohort studies and one case‐control study. No randomized trials were identified and no isolated abstracts or unpublished studies were identified that met eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty‐four studies met inclusion criteria (Figure 1). 23–54 There were 33 cohort studies and one case‐control study. No randomized trials were identified and no isolated abstracts or unpublished studies were identified that met eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Among those finding an increased risk following in vitro methods, conclusions were mixed with regard to whether the risk was due to the procedure itself or the condition of infertility. Four studies made explicit comparisons to pregnancies with a history of infertility, but not conceiving with in vitro methods 28,41,48,56 . Three 28,41,56 suggested that the increased risk of stillbirth was more related to a history of subfertility, while Wisborg et al 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though several investigations have studied maternal and perinatal outcomes of ART conception [8, 1316] or outcomes of natural pregnancy complicated by GDM [1720], to the best of our knowledge, no prospective cohort study has yet compared GDM -related outcomes between assisted conception and spontaneous pregnancies. A recent retrospective study done by Szymanska et al [21], compared maternal and neonatal outcomes of GDM between women who underwent in vitro fertilization (IVF) and non-IVF women.…”
Section: Introductionmentioning
confidence: 99%
“…Tsutsumi et al [20] studied singleton pregnancy outcomes after assisted and non-assisted reproductive technology in infertile patients. They studied Pregnancy outcome parameters such as pregnancy induced hypertension, placenta previa, placental abruption, cesarean delivery, preterm birth, very preterm birth, stillbirth, low birth weight and very low birth weight.…”
Section: Discussionmentioning
confidence: 99%